Effect of Material Type and Design on Hook Crane Performance: Stress, Deformation, and Safety Factor Analysis - Amir, Amir; Dewadi, Fathan Mubina; Aprianto, Muchammad Chusnan; Maulana, Wahyudin; Saputra, Afif; Amrulloh, Musfik; Ramadhan, Irgi; Anugraha , Antonius Apriyadi (YCMM, 2024)
This simulation aims to evaluate the stress, deformation, and strain values of the crane hook structure to ensure safe load handling and prevent functional failure. In this study, AISI 1015, AISI 1035, and alloy steel casing materials were tested, along with two different hook designs: trapezoidal and circular. The trapezoidal design had base dimensions of 34.50 mm and 58.00 mm, with a top surface area of 55.00 mm and a radius of 10.00 mm. The circular design has a diameter of 58.00 mm. Simulations were carried out using SolidWorks on AISI 1015 with Mass 10 tons, stress 279.68 N/mm², displacement 0.61 mm. on AISI 1035: Mass 12 tons, stress 310.11 N/mm², displacement 0.61 mm. on Alloy steel with Mass 8.5 tons, stress 236.87 N/mm², displacement 0.59 mm. For circular design on AISI 1015 with a mass of 9.5 tons, stress 279.69 N/mm², displacement 0.57 mm. on AISI 1035 with a mass of 10 tons, stress 310.25 N/mm², displacement 0.76 mm. Alloy steel with a mass of 8 tons, stress 237.28 N/mm², displacement 0.55 mm. Each material exhibits different mechanical characteristics, which affect stress, deformation and strain. Based on the results, the AISI 1035 material with a circular design supports a maximum load of 9.5 tons, achieving a safety factor of 1.68, which is close to the minimum threshold of 1.8 for safe operation.